Association between extreme heat exposure and acute physiological change among steel mill workers in Terengganu, Malaysia - Che Hasan, Nurul Atikah (2015)
A heat stress problem is one of the physical hazards that encountered tropical countries such as Malaysia. Most of steel mill workers were exposed to hot working condition in a different work process. The aim of present study was to identify the predicting factors of Acute Health Score (AHS). About 220 confirmed male workers were participating in this study. The WBGT index during work varied from 27.6°C to 36.2°C. All of the work stations monitored had temperatures regularly exceeded the Threshold Limit Values (TLV) of heat stress recommended by ACGIH. The most common acute health effect among the workers included heat fatigue (96.8%),lethargic (90%), dizziness (82.3%), heat cramp (58.6%), unstable movement (48.2%),and heat rashes (44.5%). The respondents were classified in a heavy metabolic workload based on their work task analysis. The physiological changes shows the significant differences of body core temperature (p<0.001), systolic blood pressure (p<0.05) and heart rate (p<0.05) before the shift starts, 2 hour of shift and at the end of the shift. The results from the study shows there was no significant correlation between WBGT Index and physiological changes of body core temperature (r=-0.23, p=0.34),systolic blood pressure (r=0.09, p=0.71), diastolic blood pressure (r=0.17, p=0.5) and heart rate (r=0.23, p=0.36). The results from the study also shows there was no significant correlation between WBGT Index and acute health score (r=-0.5, p=0.86).The regression analysis suggested sweating (p<0.05), age (p<0.05), duration of heat exposure (hours) (p<0.001) and rating of perceived exertion (RPE) (p<0.001) are the predictors factors of acute health score (AHS). The finding in this study concluded that steel mill plant considered as a hot workplace area since most of their workplaces were exceed the acceptable temperatures, 28.2°C according to (ACGIH) Threshold Limit Value (TLV). The high prevalence of acute health symptoms among the steel mill workers were heat fatigue, lethargic, dizziness, heat rashes, heat cramp and unstable movement.